Peranan Good Corporate Governance Dalam Meminimalisir Praktik Penghindaran Pajak Pada Perusahaan Go Publik - Andrew Gunawan (Owner : Riset dan Jurnal Akuntansi, 2022)
The principle of responsibility is one of the important points in the sustainability of a company. Unfortunately, this principle is often ignored, one of which is the prevalence of tax avoidance practices. Tax avoidance is not something "wrong" and violates the "law", but it is considered a bad practice from the perspective of investors' perceptions. In order to suppress this bad practice, a good governance system or what is often referred to as “Good Corporate Governance” has emerged. The results of the study found that the proportion of the board of commissioners who mastered accounting practices was unable to influence tax avoidance